Strategic Priorities of Green Companies in Indonesia - Ridloah, Siti; Wulansari, Nury Ariani; Ranihusna, Desti (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2020)
This study aims to find out what strategic priorities that green companies need in Indonesia. This type of research is exploratory research. The research method utilized in this research is qualitative clustering through 'idea networking' to obtain the strategic priorities of the company predicated on the green industry in Indonesia. The results of the study show that strategic priorities of green companies in Indonesia have several important points, namely: Excellence, Sustainability, Eco-friendly, CSR, Value Creation, Customer Focus, Efficient. It is expected to provide important information for the green industries to face the challenges. Moreover, the results of this research can be used to conduct further research on the strategic priorities of green companies in Indonesia.